Systemic Inflammatory Reaction in Females with Severe Gestosis During Surgical Delivery - I. V. Mikhno; V. M. Zhenilo (Общая реаниматология)
Objective: to study the impact the impact of surgical delivery on the time course of changes in the concentration of tumor necrosis factor-а (TNF-а), interleukin (IL)-1/8, y-interferon, IL-4, IL-6, IL-10, and neopterin in the venous blood of women with severe gestosis and to develop a method for correcting a perioperative systemic inflammatory reaction (SIR).Subjects and methods: 89 females in whom surgical delivery had been performed under spinal anesthesia were examined. A control group comprised 30 females with uncomplicated pregnancy; Group 1 included 29 females with severe gestosis; Group 2 consisted of 30 females with severe gestosis to whom the developed method of perioperative SIR correction with dexametha-sone and pentoxyphylline was applied. Solid-phase enzyme immunoassay was used to determine the peripheral blood level of the cytokines and neopterin. The study was conducted in the following steps: 1) before surgery; 2) during surgery (after aponeurosis suturing), 3), 4), and 5) on days 1, 3, and 5 postoperatively, respectively.Results. In females with uncomplicated pregnancy, surgical delivery was accompanied by increases in the concentrations of IL-1/8 and neopterin. This reaction was limited by the increased synthesis of IL-10. Beginning with the third postoperative day, there was a reduction in the level of proinflammatory cytokines. Significantly elevated venous blood concentrations of y-interferon, IL-1/8, TNF-а, IL-6, and decreased levels of anti-inflammatory cytokines, such as IL-10 and IL-4, were detectable in pregnant females with severe gestosis. Against the above background, surgical delivery caused an increase in the synthesis of proinflammatory cytokines and neopterin with the high level being within 5 postoperative days. The developed method for correction of perioperative SIR in females with severe gestosis lowered the concentrations of y-interferon, IL-1/8, TNF-а, IL-6, and neopterin and promoted the recovery of cytokine balance.Conclusion: In females with uncomplicated pregnancy, the reaction of the cytokine system during abdominal delivery is characterized by an increase in the proinflammatory potential at surgery and its reduction, beginning with the third postoperative day. This adaptive reaction of the cytokine system is aimed at enhancing the body’s anti-infectious resistance and stimulating the neuroendocrine catabolic system. Pregnancy in severe gestosis is characterized by the development of cytokine imbalance with a preponderance of proinflammatory cytokines. Surgical delivery induces activation of the mechanisms of SIR; at this background, a long phase of autoag-gression postoperatively forms, with the maximum rate being seen on the third day. The developed therapy lowers the levels of proinflammatory cytokines and neopterin, and improves T-helper cell differentiation balance, which suggests the lower activity of mononuclear phagocytes and specific cell immunity.